Cerebellar contribution to spatial realignment: A tDCS study during multiple-step prism adaptation. (April 2018) - Panico, Francesco; Sagliano, Laura; Nozzolillo, Carolina; Trojano, Luigi; Rossetti, Yves
Abstract: Several processes are devoted to error reduction in response to a visual displacement, such as the one induced by wedge prisms. Strategic calibration and spatial realignment contribute to the iteratively process that allows a progressive adjustment of motor commands to reduce the magnitude of errors. Isolating the specific contributions to motor behaviour coming from these distinct processes is not possible using traditional single-step Prism Adaptation (PA), where participants are directly exposed to full prismatic shift. Here, we selectively investigated the effect of realignment on motor behaviour by means of a PA paradigm (the multiple-step PA) that allows to elude the development of strategic calibration. We tested for a specific cerebellar contribution to realignment by means of transcranial Direct Current Stimulation (tDCS) in healthy subjects. Confirming and expanding previous imaging and stimulation results, our study causally demonstrates cerebellar involvement in spatial realignment. Additionally, our results point to a possible contribution of the cerebellum in automatic online control. The role of a cortico-cerebellar network accounting for this results and possible clinical applications are proposed and discussed. Highlights: Cathodal cerebellar tDCS during multiple-step prism exposure impaired adaptation. Stimulation interfered with both initial and late components of adaptation. The cerebellum is causally involved in spatial realignment and after-effect development. Possible cerebellar contribution to online control is discussed.